Match statistics significant to win the initial and intense rounds of a tenis tournament - Damani, Chinar; Damani, Bharat; Bagchi, Amritashish (Akademia Wychowania Fizycznego w Poznaniu)
This paper analyses the initial and intense rounds of the 2020 Australian Open Men’s Singles matches on 14 match statistics. The findings show that the statistics which are important to winning in the initial rounds are not the same as those for winning in the intense rounds. In the initial rounds, the match winner performed better than the loser on receiving points won, second serve to win, first serve to win, breakpoints won, net points won, winners, total points won, unforced errors, aces, double faults, fastest serve speed, and average first-serve speed. However, to win the intense rounds, the winner performed better than the loser on first serve to win, receiving points won and net points won. The findings help the player and the coach to develop skills and techniques to devise a player strategy during the initial rounds and the intense rounds to win the tournament.
Keywords: tennis; Australian Open; player’s strategy